تنمية الموارد البشرية و اهميتها في تحقيق التنمية المستدامة في مؤسسة اقتصادية دراسة حالة في مؤسسة مطاحن بلغيث الكبرى - - بثينة رميشي; شابي نور الهدى (My University, 2021)
The objective of this study is to identify the role that the dimensions of human resources development strategy (training, learning, development) play in achieving sustainable development in an economic institution. The study relied on a key problem:” to what extent does the human resources development strategy contribute to sustainable development in the economic enterprise.” The survey included a sample of 38 frames distributed across the study organization; in the field study the questionnaire was designed on the Lichart 5scale for the choice of the most appropriate answer, various statistical methods were used to analyze the study data. In this study the most important set of findings is that elements of human resources development strategy play an essential role in achieving the sustainable development dimensions based on the views of the sample study. The study concluded that there is a clear impact and correlation of human resource performance on the process of achieving sustainable development, as the human resource is the means of sustainable development. ................................................ تهدف هذه الدراسة إلى التعرف على الدور الذي تلعبه أبعاد إستراتيجية تنمية الموارد البشرية، )التدريب، التكوين والتعلم، التطوير في تحقيق تنمية مستدامة في مؤسسة اقتصادية. اعتمدت الدراسة على إشكالية رئيسية مفادها : "إلى أي مدى تساهم إستراتيجية تنمية الموارد البشرية في تحقيق تنمية مستدامة في المؤسسة الاقتصادية"، شملت هذه الدراسة استطلاع أراء عينة مكونة من 38 إطار موزعين على المؤسسة محل الدراسة، استخدمنا الاستبيان في الدراسة الميدانية، مصمم وفق سلم ليكارت الخماسي في اختيار الإجابة الأنسب،كما تم استخدام أساليب إحصائية مختلفة لتحليل بيانات الدراسة، تم التوصل في هذه الدراسة إلى مجموعة النتائج أهمها أن عناصر إستراتيجية تنمية الموارد البشرية تلعب دورا أساسيا في تحقيق أبعاد التنمية المستدامة حسب أراء عينة مجتمع الدراسة، حيث خلصت الدراسة إلى أن هناك تأثير واضح وعلاقة ترابط للأداء المورد البشري على عملية تحقيق التنمية المستدامة، إذ يعد المورد البشري الوسيلة و الغاية من عملية التنمية المستدامة